Hydrochlorofluoromethylation of unactivated alkenes with chlorofluoroacetic acid. Issue 47 (22nd November 2019) - Meyer, Claudio F.; Hell, Sandrine M.; Sap, Jeroen B.I.; Misale, Antonio; Peschiulli, Aldo; Oehlrich, Daniel; Trabanco, Andrés A.; Gouverneur, Véronique
Abstract: An operationally simple method enabling hydrochlorofluoromethylation of unactivated alkenes under visible light activation is reported. The procedure has various benefits. It uses commercially available and inexpensive chlorofluoroacetic acid and phenyliodine(III) diacetate for the generation of the required chlorofluoromethyl radical, it converts feedstock olefins into attractive 1-chloro-1-fluoroalkanes, and it tolerates a broad variety of functional groups. The chlorofluoromethyl radical has a reactivity profile towards alkenes similar to the nucleophilic difluoromethyl radical. Graphical abstract: Image 1 Highlights: Hydrochlorofluoromethylation in the absence of transition metal. CHFCl radical chemistry. High chemoselectivity and functional group tolerance. Operationally simple procedure. Feedstock and inexpensive starting materials and reagents.